2020
DOI: 10.1162/jocn_a_01529
|View full text |Cite
|
Sign up to set email alerts
|

Beat-based and Memory-based Temporal Expectations in Rhythm: Similar Perceptual Effects, Different Underlying Mechanisms

Abstract: Predicting the timing of incoming information allows the brain to optimize information processing in dynamic environments. Behaviorally, temporal expectations have been shown to facilitate processing of events at expected time points, such as sounds that coincide with the beat in musical rhythm. Yet, temporal expectations can develop based on different forms of structure in the environment, not just the regularity afforded by a musical beat. Little is still known about how different types of temporal expectati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 103 publications
(152 reference statements)
1
63
2
Order By: Relevance
“…To demonstrate this, in our study, we kept the nature of temporal expectations fixed, using associative temporal cues, and manipulated only the task demands. Further flexibility in the modulatory consequences of temporal expectations have been proposed when different sources of expectations are compared (e.g., associative vs. rhythmic; Triviño et al, 2011;de la Rosa et al, 2012;Breska and Deouell, 2014;Morillon et al, 2016;Breska and Ivry, 2018;Nobre and van Ede, 2018;Bouwer et al, 2020). In the current work, we focused on the modulatory consequences of temporal expectation (on both neural activity and on behavioural performance).…”
Section: Here > Discussionmentioning
confidence: 99%
“…To demonstrate this, in our study, we kept the nature of temporal expectations fixed, using associative temporal cues, and manipulated only the task demands. Further flexibility in the modulatory consequences of temporal expectations have been proposed when different sources of expectations are compared (e.g., associative vs. rhythmic; Triviño et al, 2011;de la Rosa et al, 2012;Breska and Deouell, 2014;Morillon et al, 2016;Breska and Ivry, 2018;Nobre and van Ede, 2018;Bouwer et al, 2020). In the current work, we focused on the modulatory consequences of temporal expectation (on both neural activity and on behavioural performance).…”
Section: Here > Discussionmentioning
confidence: 99%
“…Importantly, the current results extend this prior work by demonstrating that background, rhythmic cues that occur in a different modality (auditory) than the target stimuli (visual) also modulate post-perceptual ERPs. While other prior work has shown that rhythmic cues can also influence earlier N1 components associated with initial stimulus processing [8,30], the modulation of sensory/perceptual ERPs is not always observed following manipulations of temporal attention and may depend on the nature of the temporal cues or task context [22,40,[41][42][43][44]. For example, in prior studies demonstrating rhythmic effects on the N1, participants performed perceptually-demanding target detection/discrimination tasks [8,30].…”
Section: Plos Onementioning
confidence: 99%
“…It has also been suggested that manipulations of temporal attention may have their greatest effect on these later, post-perceptual stages of information processing [32,36,40]. In support of this proposal, effects of temporal orienting on early visual ERP components are not always observed and have been shown to depend on the perceptual demands of the task and the nature of the temporal orienting cues [22,32,40,[41][42][43][44]. Thus, the effect of rhythm on memory encoding could primarily reflect changes in later, post-perceptual stages of information processing.…”
Section: Introductionmentioning
confidence: 98%
“…Prior studies have shown later ERP components 86 associated with post-perceptual stimulus identification and evaluation (e.g., N2, P3) [31][32][33][34][35] are 87 sensitive to temporal orienting cues that direct attention to particular moments in time [30,36,37].88 It has also been suggested that manipulations of temporal attention may have their greatest effect 89 on these later, post-perceptual stages of information processing [30,34,38]. In support of this 90 proposal, effects of temporal orienting on early visual ERP components are not always observed 91 and have been shown to depend on the perceptual demands of the task and the nature of the 6 92 temporal orienting cues [19,30,[38][39][40][41][42]. Thus, the effect of rhythm on memory encoding could 93 primarily reflect changes in later, post-perceptual stages of information processing.…”
mentioning
confidence: 99%
“…This finding is consistent with prior 411 work demonstrating effects of temporal attention on visually-evoked N2 and P3 components 412 [30,36,37], and reveals that temporal cues provided by musical rhythm influence post-perceptual 413 visual processing. While rhythmic temporal cues have also been shown to influence the 414 amplitude of earlier N1 components associated with initial stimulus processing [7,27], the 415 modulation of sensory/perceptual ERPs is not always observed following manipulations of 416 temporal attention and may depend on the nature of the temporal cues or task context [19,[38][39][40][41][42].…”
mentioning
confidence: 99%